THE EFFECTS OF GOOGLE TRANSLATE APPLICATION ON ENGLISH VOCABULARY MASTERY OF HIGH SCHOOL STUDENTS - Milda Ningsih Samir; Muhammad Basri; Andi Muliati (State University of Makassar, 2023)
The study aims to determine the effects of translation apps on English vocabulary mastery of high school students. The method of this study was a Pre-Experimental design that consisted of one experimental class. The samples in this study were XII MIA SETIA students from SMAN 25 BONE. Samples were selected using a cluster random sampling technique with a total number of 17 students. The instrument for collecting data was Pre-test and Post-test. Based on calculations, the mean scores of post-test in the experimental class was 87.5. The results of the statistical hypothesis test using the paired sample t-test revealed the probability/significance level is less than the alpha level. Thus, the use of google translate has a positive effect on high school students English vocabulary mastery. Keywords— Vocabulary, Google Translate Application.